Analytical Modeling of Oscillations of Movable Operating Elements of a Roll-Drum Activator - Krot, Alexander; Ruchka, Artem; Savchenko, Alexander; Krot, Olga; Supryaga, Dmitry (International Journal of Engineering and Technology, 2018)
The article investigates the equipment for mechanical activation of building mixtures and the effect of the resulting oscillations on the activation efficiency and on the stability of the equipment operation. The activation of the entire building mixture with filler and wetted by finite amount of water can solve many problems that determine the quality of bricks or materials. Carried out researches of harmful oscillations of working of roll-drum activator (RDA) and their effects on the quality of processing. The own frequency of free oscillations arising in the RDA during its operation was determined experimentally. The possibility to stabilize the machine by installing shock absorbers has been examined. The influence of unwanted oscillations on the quality of products has been examined; the most optimal stabilization of the movement of "lever – roll" by using of additional external oscillations on the system has been defined. The analytical model of law of motion of the system with external oscillations and the parameters of its oscillations has been obtained. The parameters of oscillations of the roll has been determined; it was confirmed that the external oscillations have a positive effect on the efficiency of the activation and product quality.